Rejection sensitivity mediates the interparental conflict and adolescent Internet addiction: School connectedness as a moderator - Tao, Zhiyuan; Zhao, Xiuli; Wang, Zhenhai; Yu, Chengfu; Zhang, Wei (Frontiers in Psychology, 2022)
Internet addiction (IA) is a growing social problem with negative mental and social outcomes, present study examined whether rejection sensitivity mediates the relationship between interparental conflict and adolescent IA and the moderating role of school connectedness. 1007 adolescents (51.84% females; Meanage = 13.17; SD = 0.69) anonymously completed questionnaires to assess interparental conflict, school connectedness, rejection sensitivity, IA and demographic information. The cross-sectional results of regression-based analyses showed that: (1) the positive association between interparental conflict and adolescent IA was partially mediated by rejection sensitivity; (2) this indirect link was moderated by the school connectedness and was stronger for adolescents with high school connectedness. The results provide support for the attachment theory that high interparental conflict could increase adolescents’ rejection sensitivity, and high school connectedness plays a double-edged role that adolescents show more rejection sensitivity while reporting high interparental conflict and high school connectedness.